WorldFish – Weather Forecasting Prototype - Mudege, N.N. (2024)
WorldFish developed a prototype for the Aquaculture Advisory Tool for hosting iSAT. The prototype has demonstrated that the platform can send messages and be stable when linked to weather data/ information sources to generate advisories for aquaculture farmers. The prototype is linked to the AI Model the team developed for the air and pond water temperature algorithm.